Construction of retaining wall for Residential at Bukit Mahkota, Bangi / Muhammad Akmal Azman - Azman, Muhammad Akmal (2017)
Practical Training (BS 360) is the main core subject for the Final Year Student of Diploma in Building Surveying, in UiTM Perak. This course was consisting of 8.0 credit hours, semester 6. Practical Training refers to experience that is relevant to professional development prior to graduation. One of the requirements for students of Diploma in Building Surveying to complete the program is the students must complete at least 14 weeks of Practical Training. It started on 1st Dec 2016 until 31th Mar 2017, which means it is 4 months doing the Practical Training . Student can have more knowledge the aspects of organizational management, technology, design, property, building economic and financing , law, communications, project planning and management and I have learnt many thing during practical training. This practical training makes the student experience the real work situation at the company of their practical.